Recent developments in biomedical applications of metasurface optics - Cheng Hung Chu; Sunil Vyas; Yuan Luo; Pan-Chyr Yang; Din Ping Tsai (APL Photonics, 2024)
Metasurfaces have attracted considerable attention because of their unique optical capabilities to control the fundamental properties of light, such as amplitude, phase, and polarization. The flat nature of metasurfaces can help reduce the complexities and bulk of conventional optical systems. After a decade of rapid progress, metasurfaces are close to maturity and have found their role in various optical applications. This review emphasizes the significant advancements and emerging applications of metasurfaces in biomedical optics, particularly focusing on beam shaping for laser treatments, light-sheet fluorescence microscopy, HiLo microscopy, and optical trapping. Looking forward, we discuss foreseeable challenges for integrating metasurfaces into biomedical, preclinical, and clinical systems.